2022
DOI: 10.3390/antiox11122441
|View full text |Cite
|
Sign up to set email alerts
|

Eco-Efficient Quantification of Glucosinolates in Camelina Seed, Oil, and Defatted Meal: Optimization, Development, and Validation of a UPLC-DAD Method

Abstract: Camelina sativa (camelina) seed, oil, and defatted meal are widely used for food, animal feed, and other purposes. The accurate quantification of camelina glucosinolates is critical as their functionalities are highly dose-dependent. The classic quantification of glucosinolates in camelina products involves tedious desulfation steps, toxic reagents, and a lengthy instrument time because glucosinolates are easy to degrade and subject to interference in the liquid chromatography. Thus, we developed and validated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Camelina seeds are characterised by the presence of aliphatic glucosinolates: 9-(methylsulfinyl)nonyl glucosinolate (also known as glucoarabin or GS9), 10-(methylsulfinyl)decyl glucosinolate (also known as glucocamelinin or GS10) and 11-(methylsulfinyl)undecyl glucosinolate (also known as homoglucocamelinin or GS11) (41,42) . Depending on their nature, glucosinolates can either be hydrolysed by myrosinases which can be produced by gut microorganisms (43) producing progoitrin which is spontaneously converted into goitrin at neutral pH and into nitriles at a more acidic pH (< 5·5) (44) , or they can be degraded into isothiocyanates and then to indole-3-carbinol by the release of thiocyanate at neutral pH, and to indole-3-acetonitrile at acidic pH (4–5·6) (45,46) .…”
Section: Discussionmentioning
confidence: 99%
“…Camelina seeds are characterised by the presence of aliphatic glucosinolates: 9-(methylsulfinyl)nonyl glucosinolate (also known as glucoarabin or GS9), 10-(methylsulfinyl)decyl glucosinolate (also known as glucocamelinin or GS10) and 11-(methylsulfinyl)undecyl glucosinolate (also known as homoglucocamelinin or GS11) (41,42) . Depending on their nature, glucosinolates can either be hydrolysed by myrosinases which can be produced by gut microorganisms (43) producing progoitrin which is spontaneously converted into goitrin at neutral pH and into nitriles at a more acidic pH (< 5·5) (44) , or they can be degraded into isothiocyanates and then to indole-3-carbinol by the release of thiocyanate at neutral pH, and to indole-3-acetonitrile at acidic pH (4–5·6) (45,46) .…”
Section: Discussionmentioning
confidence: 99%
“…In general, cold temperature limits spurious changes in metabolites owing to biochemical reactions or thermal lability that could affect the integrity of metabolomic profiles [49,50]. In the specific case of glucosinolates, some studies confirmed that inorganic solvents maintained at cold temperatures prevent their degradation by the myrosinase enzyme [51][52][53]. In brief, shoots were crushed in mortar filled with liquid nitrogen and 215.35 ± 10.38 mg of fresh mass was transferred to a 2 ml Eppendorf tube.…”
Section: Untargeted Metabolomic Extractionmentioning
confidence: 99%
“…The unique fatty acid composition of camelina oil has favorable nutritional and physiological effects, such as reducing blood triglyceride and cholesterol levels. As a result, camelina oil is considered suitable for direct consumption, cooking, and as an enrichment ingredient in products such as margarine, salad dressing, mayonnaise, and ice cream, providing omega-3 fatty acids (Meza et al 2022;Li et al 2023).…”
Section: Introductionmentioning
confidence: 99%